2012
DOI: 10.1007/jhep01(2012)069
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the bottom-quark forward-central asymmetry at the LHC

Abstract: Measurements of the top quark forward-backward asymmetry performed at the Tevatron suggest that new-physics may be playing a role in tt production. To better understand the source of the asymmetry, recent proposals have called for a measurement of the bottom and charm forwardbackward asymmetries at the Tevatron, using jets with embedded muons. Here we propose a corresponding measurement of the bottom quark forward-central asymmetry designed to look for similar effects in the b-sector at ATLAS and CMS. We const… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…In the fourth column the first uncertainty is due to neglect of higher-order terms, and the second is the combined scale uncertainty. The uncertainty in the O(α 2 /α Based on CDF's expected sensitivities [7] and assuming the Standard Model (and the measurements follow a Gaussian distribution), CDF should be able to exclude A It has been suggested [5,6] that measuring the charm-quark forward-backward asymmetry at the Tevatron (A , the kinematic regions where the asymmetry becomes a few percent have small production cross sections, and will require the LHC to run for at least a year at 14 TeV to collect enough data for the SM asymmetry to be statistically distinguishable from zero. Furthermore, the EW contribution to the cross section in these kinematic regions is negligible, and no Zresonance effects are expected.…”
Section: Standard Model Calculationmentioning
confidence: 99%
“…In the fourth column the first uncertainty is due to neglect of higher-order terms, and the second is the combined scale uncertainty. The uncertainty in the O(α 2 /α Based on CDF's expected sensitivities [7] and assuming the Standard Model (and the measurements follow a Gaussian distribution), CDF should be able to exclude A It has been suggested [5,6] that measuring the charm-quark forward-backward asymmetry at the Tevatron (A , the kinematic regions where the asymmetry becomes a few percent have small production cross sections, and will require the LHC to run for at least a year at 14 TeV to collect enough data for the SM asymmetry to be statistically distinguishable from zero. Furthermore, the EW contribution to the cross section in these kinematic regions is negligible, and no Zresonance effects are expected.…”
Section: Standard Model Calculationmentioning
confidence: 99%
“…There is also some interest in measuring the charge asymmetry in charm-quark production [8,9], and LHCb may well have the charm-tagging capabilities to do so.…”
Section: B Charm-quark Charge Asymmetrymentioning
confidence: 99%
“…1. In [60][61][62][63][64][65][66][67][68][69][70][71], comparisons between different models are carried out, and study of those models or measurements in the LHC context can be found in [72][73][74][75][76][77][78][79][80][81][82][83][84].…”
Section: Introductionmentioning
confidence: 99%